Tren Toxic Productivity Sebagai Gejala Terjadinya Burnout Syndrome Terhadap Prestasi Akademik pada Remaja Rentang Usia 18-23 Tahun di Kota Bandung - Alni Tsabita; Febi Febriyanti; Siti Komariah; Sri Wahyuni (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
This research discusses the phenomenon of toxic productivity in teenagers aged 18-23 years who are classified as pupils and university students. It was found that one of the causes of toxic productivity is fear and anxiety about lagging behind other people's achievements, apart from that, the toxic productivity that is being experienced is also a cause of burnout syndrome. The aim of this research is to reveal the factors behind the influence of toxic productivity on academic achievement for pupils and students and how it influences the learning process in the classroom. This research method uses a descriptive qualitative approach, where the data sources used are supported by systematic and objective analysis of text content, such as articles, news, interviews, or notes, to identify the phenomenon that is the focus of the research. The results of the research show that the toxic productivity trend occurs due to the FOMO (fear of losing moment) phenomenon which is consumed by many teenagers on social media, especially those related to achievement, efforts to be equal to or more than what other people have achieved, which often leads to burnout.